A comparison between the designs of flexural timber members based on eurocode 5 and the Malaysian timber code MS 544: 2001 - Sheikh, Shujaatullah (2014)
For years, MS 544 has served as the code of practice for Malaysian engineers designing structural timber members using local timber species The permissible stress design (PSD) code was published in 1978 by the Department of Standards Malaysia and is closely modelled after the now obsolete British Standards code of practice CP 112. Subsequently, the department published a revised edition of MS 544 in 2001 with minor changes concerned mostly with strength grouping of Malaysian timber species used for structural purposes. However, as the world moves rapidly towards globalisation and the international engineering community having long since embraced limit state design philosophy with the advent of the concrete design code CP 110 in 1972, it is high time that Malaysian engineers do the same for structural timber by adopting the modem code of practice EN 1995-1-1. This code, also known as Eurocode 5, has been used in the United Kingdom and much of Western Europe for at least the past five years.This paper seeks to compare MS 544: 2001 and Eurocode 5 in terms of design philosophy and methodology, and highlights the similarities and differences between the two codes of practice, in particular for the design of flexural members. Flow charts and worked examples are also mcluded to further illustrate the workings of both codes of practice.